Historicist Architecture as an Example of a Process of Cultural Exchange: Reception of French Modern Architecture Within Nineteenth-Century Historicism in the Bohemian Lands and in a Broader European Context - Klinerová, Adéla (Dějiny – teorie – kritika, 2019)
This contribution analyses the reception of French modern architecture in nineteenth-century historicism, treating it as a case of cultural exchange. Historicisist architecture inspired by French models was explored mainly in international studies written in the 1970s and 1980s. Nevertheless, a reinterpretation of historicist architecture through the prism of current methodological frameworks offers new perspectives and the same holds of a comparative approach which takes into account a wider European context. This study first addresses the issue of inconsistent terminology, thus coming to terms with the existing scholarly literature. Since this subject involves work with historical models originating in a particular cultural environment, one ought to consider the extent to which the actors could have been sufficiently familiar with the relevant models and the communication channels which may have contributed to their circulation. The particular factors which conditioned or enabled cultural transfer are presented in two case studies which focus on situation in the Bohemian Lands. Of importance was direct experience of the French environment, training in architecture, the person who commissioned a particular project, the personality of the architect, as well as the availability of theoretical literature and graphic images. In the final part of the contribution, the author outlines some directions in which this research could develop. She points out, for instance, that transfer may have been either direct or mediated by other cultural centres, whereby in case of mediated transfer, particularly the Viennese environment of the second half of the nineteenth century seems to have played a crucial role.